2013
DOI: 10.1371/journal.pcbi.1002874
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Effects of Different Admission Screening Strategies to Control the Spread of Methicillin-resistant Staphylococcus aureus

Abstract: Nosocomial infection rates due to antibiotic-resistant bacteriae, e.g., methicillin-resistant Staphylococcus aureus (MRSA) remain high in most countries. Screening for MRSA carriage followed by barrier precautions for documented carriers (so-called screen and isolate (S&I)) has been successful in some, but not all settings. Moreover, different strategies have been proposed, but comparative studies determining their relative effects and costs are not available. We, therefore, used a mathematical model to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Recent studies reported that selective MRSA screening to high-risk colonization patients (e.g., patients at intensive care unit admission) and patients detected as MRSA carrier previously will reduce the prevalence of MRSA more efficiently than universal screening at hospital admission. 6,39 Such a strategy should also be developed for other settings. In addition, it is necessary to study clinical isolates and the burden of disease caused by MRSA in Indonesian hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that selective MRSA screening to high-risk colonization patients (e.g., patients at intensive care unit admission) and patients detected as MRSA carrier previously will reduce the prevalence of MRSA more efficiently than universal screening at hospital admission. 6,39 Such a strategy should also be developed for other settings. In addition, it is necessary to study clinical isolates and the burden of disease caused by MRSA in Indonesian hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, the incidence of methicillin-resistant S. aureus (MRSA) in surgical site infections, bloodstream infections, and pneumonia has increased significantly 2,3 . MRSA strains are considered to be endemic in many hospitals throughout the world and are now responsible for approximately 40-60% of healthcare-associated infections 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently published studies incorporated the interaction between ICUs and general wards, or between general wards within a hospital. 35,40,49,72,73 Donker et al 74 was the first study to look at the impact of different referral patterns among various categories of hospitals on MRSA infection rates. One year later, 2 additional studies examined the interaction between the settings for MRSA.…”
Section: Setting and Interaction Between Settingsmentioning
confidence: 99%
“…83,84 Recently published studies paid more attention to the economic aspect of HAIs. They have estimated costeffectiveness for different IPC strategies and investments, mainly for MRSA 59,[71][72][73]85,86 followed by CD. 82,87 Economic analyses were carried out for a single intervention (ie, hand hygiene, 59,71 isolation, 59 vaccination, 70,87 patient room design 56 ), combination of 2 59,73 or 3 interventions, 85,86 and a bundled strategy.…”
Section: Economic Evaluationmentioning
confidence: 99%